New species of Xiphocentron Brauer 1870 (Trichoptera: Xiphocentronidae) from Northeastern Brazil - Vilarino, Albane; Calor, Adolfo R. (Zootaxa, 2015)
Two new species of Xiphocentron (Trichoptera: Xiphocentronidae) from Northeastern Brazil are diagnosed, described, and illustrated. Xiphocentron (Antillotrichia) kamakan n. sp. has inferior appendages each with a shape discontinuity (twist) between the first and second articles of inferior appendage, similar to that found in X. (Antillotrichia) rhamnes Schmid 1982, X. (Antillotrichia) serestus Schmid 1982, and X. (Antillotrichia) mnesteus Schmid 1982; however, it can be distinguished from these species by each inferior appendage having two darkly sclerotized spinulous regions ventrally on the basomesal and midmesal margins. Xiphocentron (Antillotrichia) maiteae n. sp. can be differentiated from all other congeners by having the basoventral margin of each inferior appendage strongly produced posterad. A key to males of Brazilian species of Xiphocentron is provided.